Concussion history and heart rate variability during bouts of acute stress - Harrison, A.; Lane-Cordova, A.; La Fountaine, M. F.; Moore, R. D. (Journal of Athletic Training, 2022)
Context After a sport-related concussion, many athletes experience persisting neurophysiological alterations. These alterations may be absent at rest but emerge during moments of physiological stress. Unnoticed and untreated neurophysiological dysfunction may negatively affect long-term neurologic health in adolescent athletes, as they are at a critical point in development.